Goethe et Götz. Prothèse adorée, prothèse redoutée. Ambivalence et autonomisation d’une main de fer dans un drame chevaleresque - Géraldine Ponsolle (Cahiers du MIMMOC)
From historical figure to Goethean legend, Götz von Berlichingen was a fictional hero, for himself, for Germanic culture and for the young and passionate Johann Wolfgang von Goethe. His iron hand, by turns a reminder of weakness, an object of true adoration and an instrument of superhuman power, turns out to confer a hybrid identity on its bearer. With Goethe, this hero of the Sturm und Drang crosses the boundaries of the theatre to give birth to a world of symbols and magic. The prosthesis is no less manipulable and fallible. Götz, the representative of a bygone chivalry, suffers the constraints and betrayals of his time. He is condemned by his own obsolescence and that of his prosthesis.